Aging, Death, and the Completion of Being - Van Tassel, David D. (University of Pennsylvania Press, 2016)
These essays introduce a humanistic perspective to the study of aging. The assumption behind this work is that in history, literature, folklore, and art we have the record of centuries of human experience to enhance our present understanding of aging, old age, and death.